Aproveitamento integral do abacaxi na produção de vinagres enriquecidos com extrato de folhas de Syzygium malaccense (L.) Meer. & L.M. Perry - Bertan, Fernanda Aparecida Brocco (2021)
Pineapple (Ananas comosus (L.) Merril) is a tropical fruit accepted worldwide and rich in phytochemicals that contribute to the prevention of numerous diseases. However, parts of the fruit, such as the peels, are commonly discarded, generating residues that require treatment. Thus, in a context of a circular economy, it is important to develop products that help to make better use of the fruit and reduce waste. In this sense, the present work’s objective was to use both the pineapple pulp and peels in the production of wines and gourmet vinegars, enriched with red-jambo leaf extract (Syzygium malaccense (L.) Merr. & LM Perry) rich in phenolic compounds and antioxidants. A commercial strain of Saccharomyces cerevisiae r.f. bayanus, and wild strains of acetic acid bacteria isolated from “colonial vinegar”, were used in the fermentations to produce alcohol and acetic acid, respectively. Alcoholic fermentations were carried out at 28 ºC using a pulp or peels -based wort in a bucket fermenter with an airlock. Fermentations with pineapple pulp resulted in an ethanol yield of 0.28 g/g (YP/S), a volumetric productivity of 0.55 g/Lh (QP), and an efficiency of 54.8% (n). Fermentations with peels resulted in ethanol yields of 0.27 g/g, a productivity of 0.48 g/L.h, and an efficiency of 52.8%. Fermentations with the acetic acid bacteria were carried out in the traditional system (Orleans process) in a Grapia barrel at 28 ºC. Contents of 5.5% (v/v) and 4.5% (v/v) of acetic acid resulted from acetification of pineapple pulp and peel, respectively. Both pulp and peel wines presented appreciable phenolic contents (188.97 mg GAE/L and 110.53 mg GAE/L) and antioxidant potential. Pulp and peel vinegars had higher levels of total phenolic compounds (364.45 mg GAE/L and 222.94 mg GAE/L) and high DPPH and ABTS radical scavenging capacity compared to the wines. The peel wines showed greater lightness (L*) and higher saturation index (C*) and its color tended more towards yellow compared to the pulp wines. Acetification led to a reduction in the saturation index (C*) of the vinegar samples in relation to wines and led to an intensification in the color tone (hue angle) in the peel vinegar samples. All vinegars showed antimicrobial potential with biocidal activity against bacteria: Staphylococcus aureus, Bacillus subtilis, Salmonella enterica Typhimurium, and Candida tropicalis and Candida albicans yeasts. The enrichment of the vinegars with the red-jambo leaf extract promoted an increase in the content of polyphenols and antioxidant activity, and also enhanced the antimicrobial activity of peel vinegar against Staphylococcus aureus.